VIBRATIONS OF PIECE-HOMOGENEOUS PLATES - Khadjieva , Salima Sadikovna (Educational Research in Universal Sciences, 2023)
The article presents in a general three-dimensional formulation the problem of oscillation of two-layer piecewise homogeneous viscoelastic plates of constant thickness. General vibration equations are derived, expressions are given for displacements and stresses at internal points of the plate in terms of functions describing displacements and deformations of the points of the contact plane